PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP KEGIATAN JUAL BELI PADA MATA PELAJARAN IPS KELAS III SEKOLAH DASAR - Zerri Rahman Hakim; Taufik Taufik.; Qurrotul Aini (Universitas Syiah Kuala, 2018)
The research in inteded to know the understanding concept buying and selling activities in IPS (social studies) subject learning that cooperative learning type talking stick modelis better than the conventional model. The research method used is quasi experimental with non-equivalent control group research design, sampling was done by using purposive sampling tehnique. The selected sample is class III A student as the control group that get a conventional model as the the treatment and class III B is an experimental class that get cooperative learning type talking stick model as the treatment. Based on the post –test data analysis, it showed that the average of control gorup student understanding concept is 60,50 while the experimental class is 85,50 it can be seen from the result of the right example test , the result of tcount ttable or 3,43 2,00 with a significant level of 0,05. Based on the results of research that has done, it can be concluded that the student understanding concept buying and selling activities IPS (social studies) subject the applied cooperative learning type talking stick model better than student that applied conventional model.